Philosophy of care - Grojs, Boris 1947- (Verso, 2022)
"Our current culture is dominated by the ideology of creativity. One is supposed to create the new and not to care about the things as they are. This ideology legitimises the domination of the "creative class" over the rest of the population that is predominantly occupied by forms of care - medical care, child care, agriculture, industrial maintenance and so on. We have a responsibility to care for our own bodies, but here again our culture tends to thematize the bodies of desire and to ignore the bodies of care - ill bodies in need of self-care and social care. But the discussion of care has a long philosophical tradition. The book retraces some episodes of this tradition - beginning with Plato and ending with Alexander Bogdanov through Hegel, Heidegger, Bataille and many others. The central question discussed is: who should be the subject of care? Should I care for myself or trust the others, the system, the institutions? Here, the concept of the self-care becomes a revolutionary principle that confronts the individual with the dominating mechanisms of control"--
Keywords: Philosophie; Sorge; Pflege; Caring; Humanité (Morale); PHILOSOPHY / Ethics & Moral Philosophy